Rural Development in Hungary - Kovács, Teréz (Discussion Papers, 2012)
The first part of the study provides a situation analysis of Hungarian agriculture on the basis of data from the General Agricultural Survey of 2000, followed by the presentation of positive and negative phenomena experienced by post-socialist rural society. The second major part is devoted to the specifics of differentiated development patterns of rural areas and the emergence of integrated rural development. The study also contains a detailed analysis of the SAPARD programme. Hungary experienced a strong migration flow in the era of post-socialism from cities towards villages. Migration was differentiated: members of the urban middle class migrated to suburban areas, while poor urban dwellers moved to remote lagging villages. Lagging villages have become major destination points of foreign (mostly retired) immigrants.